Implementación de un software para controlar los ordenadores del laboratorio de informática del bachillerato y su influencia en el proceso de enseñanza aprendizaje del Colegio República del Ecuador sección matutina de la ciudad de Machala, periodo lectivo 2012-2013. - Cuenca Jumbo, Gustavo (2013)
This degree work trying to solve a problem within the educational environment in the subject. Implementation of a software to control computers of high school computer lab and its influence on the process of teaching and learning the Republic of Ecuador Machala City College.